53.0k views
2 votes
Solve by elimination

Solve by elimination-example-1

1 Answer

1 vote

Answer:(4,1)


Explanation:

-x+3y=-1

X-2y= 2

______

Change second equation move all to right side to leave x on left side .

-x+3y= -1

X= 2y+2


Now substitute second equation that you made into first equation to find y.

-(2y+2)+3y= -1

-2y-2+3y=-1

Y-2=-1

Y= -1+2

Y= 1

Now substitute your answer of y into second equation you created to find x .

X= 2y+2

X= 2(1)+2

X=2+2

X=4


User MiniGunnR
by
4.3k points